Associations between homocysteine, vitamin B12, and folate and the risk of all-cause mortality in American adults with stroke - Zhang, Panpan; Xie, Xia; Zhang, Yurong (Frontiers in Nutrition, 2023)
Objective: Associations between plasma homocysteine (Hcy), vitamin B12, and folate and the risk of all-cause mortality are unclear. This study aimed to examine whether plasma Hcy, vitamin B12, and folate levels independently predict the risk of all-cause mortality in American adults with stroke.Methods: Data from the United States National Health and Examination Survey (NHANES) (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) were used and linked with the latest (2019) National Death Index (NDI). Cox proportional hazards models and restricted cubic splines were used to estimate the hazard ratios (HR) and 95% confidence intervals (CI) of all-cause mortality for Hcy, folate, and B12 levels in adults with stroke.Sample weights were calculated to ensure the generalizability of the results.Results: A total of 431 participants were included (average age: 64.8 years). During a median follow-up of 10.4 years, 316 deaths occurred. Hcy was positively associated with all-cause mortality in adults with stroke (HR, 1.053; 95% CI: 1.026-1.080). Stroke patients with plasma Hcy levels in the fourth quartile had a 1.631-fold higher risk of all-cause mortality (HR, 1.631; 95% CI: 1.160-2.291) than those in the first quartile. The association between plasma Hcy and all-cause mortality was strong significant in older patients (p for interaction =0.020). Plasma folate and vitamin B12 concentrations were inversely correlated with Hcy concentrations (B-value (95%